Blended Learning Model Implementation Study to Improve Learning Outcomes Elementary School Student Mathematics - Sidik, Ghany Taufik; Iswara, Prana Dwija; Herman, Tatang (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2022)
The background of this study is the low completion of student learning outcomes against five competencies in Mathematics lessons at the elementary school level. The use of teacher strategies is undoubtedly a critical consideration in overcoming the low learning outcomes of Mathematics at the elementary school level. Learning strategies using technology-based media that combine face-to-face learning in schools and remote online education expect to be a solution for teachers in overcoming the low outcomes of learning Mathematics at the elementary school level. Therefore, the author's purpose in researching this article is to examine implementing the Blended Learning model to improve mathematics learning outcomes for elementary school students. The method used by the author in this study is the systematic literature review method. Researchers reviewed 5 research articles on the Blended Learning model's implementation in mathematics published from 2019 to 2021 in elementary schools. The technique applied by the author in collecting data is the documentation technique. Then the instrument used by the author in this study is in the form of a list of classification order of research materials based on a research study focus and the format of research notes. This study resulted in a significant increase in the completeness of student learning outcomes in 5 different elementary schools from 5 researchs caused by teachers choosing to implement the Blended Learning model in Mathematics lessons.